KORELASI KADAR ION LOGAM Pb TERHADAP KADAR PROTEIN PADA KERANG TAHU(Meretrix meretrix) YANGDIAMBIL DI PERAIRAN PANTAI BUNYU KALIMANTAN UTARA - Edi Novian Jaya; Rudi Kartika; Chairul Saleh (PROSIDING SEMINAR KIMIA, 2017)
The Research on "Correlation Pb metal ion concentration the protein content in the shells Tahu (Meretrix meretrix) taken in coastal waters Bunyu Island North Borneo". This study aims to determine the levels of metal ions Pb and protein levels in Shell tahu based on the size and area of different sampling. Then the metal ion content of Pb and protein correlated using Least Square method. Analysis of Pb metal ion levels by using AAS (Atomic Absorption Spectrophotometer) and analysis of protein content using the Kjeldahl method. In this study, the levels of metal ions Pb at area 1 with an average of 0.638 mg / L, the levels of metal ions Pb at area 2 with an average of 0,940 mg / L, the levels of metal ions Pb in area 3 with an average of 0.664 mg / L. The protein content of the mussels out in area 1 with an average of 13.9244%, protein content in area 2 obtained an average protein content of 20.3020% and area 3 obtained an average protein content of 16.1540%. Correlation Pb levels against the protein content of the Shells tahu (Meretrix meretrix) r = 0.856 Keywords: Metal Pb, Protein, Shells Tahu (Meretrix meretrix), AAS (atomic absorption spectrophotometer), Kjeldahl Method